Effect of the finite conductivity of a metal on properties of a magnetostatic backward volume wave in layered metallized structures - Khivintsev, Yuri Vladimirovich; Vysotskii, Sergei Lvovich; Dzhumaliev, Aleksandr Sergeevich; Filimonov, Yuri Aleksandrovich (Известия Саратовского университета. Новая серия Серия: Физика, 2023)
Background and Objectives: Layered structures based on ferrite and metal films are actively studied in magnonics. Usually, the effects associated with the finite conductivity of the metal are not taken into account. The aim of this work was to investigate the influence of the thickness of a metal with finite conductivity on the dispersion and damping of a magnetostatic backward volume wave (MSBVW) in the ferrite-metal and ferrite-insulator-metal structures. Materials and Methods: The dispersion equation for MSBVW was derived using Maxwell’s equations in the magnetostatic approximation, the Landau-Lifshitz equation, and standard electrodynamic boundary conditions. Calculations were performed for the structures based on yttrium iron garnet (YIG) films with metal resistivity characteristic of silver, indium, and copper. Results of the calculation we compared with results of an experiment on MSBVW propagation in a YIG film metallized by copper performed using a vector network analyzer and microstrip antennas for excitation and detection of the MSBVW. Results and Conclusions: It was found that, the metallization always suppresses MSBVW propagation, and at metal thicknesses t ≥ 10 nm, the ohmic losses due to the metal significantly exceed the intrinsic magnetic losses in the ferrite. It was also shown that the gap between the ferrite and metal can be used to suppress the long-wavelength part of the MSBVW spectrum.